Designing Islamic Boarding School with Green Architecture Approach in Medan City - Rahman, Vinky; Sari, Audry Claudya (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Islamic boarding schools are the oldest religious educational institutions in Indonesia. Initially, they focused on spiritual science. But as time went by, general education also developed in it. Islamic boarding school education helps students balance religious knowledge and general knowledge, as well as form good character. Locations that interfere with the learning process. In addition, many students from outside the city feel lonely and stressed. Therefore, a comfortable environment is needed. Implementing Green architecture can create a positive physical and social environment in Islamic boarding schools. Green plants provide tranquility and green architecture encourages environmental awareness for students and the surrounding community.